2013
DOI: 10.1074/jbc.m112.409441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transaldolase Activity in the Isolated Heart Supplied with [U-13C3]Glycerol

Abstract: Background:The metabolic fate of glycerol in the heart is controversial. Results: [U-13 C 3 ]Glycerol is metabolized to glycogen, but the label is only found in carbon positions 4 -6 of each glucose moiety. Conclusion: This isotopomer pattern can only be ascribed to transaldolase activity. Significance: This is the first detection of transaldolase activity of an isolated organ using a stable isotope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…184 Myocardial glycogen turnover can also be estimated though simultaneous assessment of net 14 C-labeled glucose into glycogen and total glycogen content; this modified protocol has suggested that specific perfusion conditions (such as simultaneously elevated insulin and acetoacetate levels) may accelerate glycogen turnover in the rat heart, 69 and exposed the dynamic nature of myocardial glycogen turnover. Lastly, elevated levels of GLUT4 during reperfusion facilitate the replenishment of glycogen pools after myocardial ischemia, which further underscores the need for methods to assess glycogen metabolism in the heart.…”
Section: Turnover Of Intracellular Macromolecules: Proteins Glycogenmentioning
confidence: 99%
“…184 Myocardial glycogen turnover can also be estimated though simultaneous assessment of net 14 C-labeled glucose into glycogen and total glycogen content; this modified protocol has suggested that specific perfusion conditions (such as simultaneously elevated insulin and acetoacetate levels) may accelerate glycogen turnover in the rat heart, 69 and exposed the dynamic nature of myocardial glycogen turnover. Lastly, elevated levels of GLUT4 during reperfusion facilitate the replenishment of glycogen pools after myocardial ischemia, which further underscores the need for methods to assess glycogen metabolism in the heart.…”
Section: Turnover Of Intracellular Macromolecules: Proteins Glycogenmentioning
confidence: 99%
“…13 C enrichment in glycogen or in the glycerol moiety of acylglycerols was measured as described previously (23)(24)(25). Briefly the 13 C enrichment in glycogen was calculated by the sum of the following isotopomers measured in glucosyl units: [ 13 C in glycogen or the glycerol moiety of acylglycerols in muscle was assumed to originate from lactate and blood glucose.…”
Section: Enrichment In Glycogen and In The Glycerol Moiety Of Acylgmentioning
confidence: 99%
“…The three-carbon unit can then condense with glyceraldehyde 3-phosphate (GA3P) to yield fructose 6-phosphate (F6P) and erythrose 4-phosphate. The transaldolase reaction also directly exchanges carbons 4 -6 of F6P with GA3P (12)(13)(14)(15)(16)(17). The fourth relevant pathway involves possible redistribution of carbon tracers in the oxidative arm of the PPP.…”
mentioning
confidence: 99%